Low-level Mercury Exposure and Risk of Asthma in School-age Children. Issue 5 (September 2015) - Kim, Kyoung-Nam; Bae, Sanghyuk; Park, Hye Yin; Kwon, Ho-Jang; Hong, Yun-Chul
<x xml:space="preserve">Abstract</x> Background: Mercury (Hg) has been reported to have adverse effects on the immune system. However, the association between Hg exposure and asthma remains unclear. We hypothesized that blood Hg concentrations are associated with asthma and immune system blood profile changes in school-age children. Methods: Between 2005 and 2010, we evaluated 4, 350 Korean children at 7–8 years of age with no previous asthma diagnosis. Follow-up surveys were conducted twice, each 2 years apart, until 11–12 years of age. For every survey, we evaluated asthma through a questionnaire and blood profile. We analyzed the association of Hg concentration with asthma by logistic and Cox regression models and the association with blood profile by generalized additive and linear mixed models. Results: Blood Hg concentrations at 7–8 years of age were associated with an increased risk of asthma (odds ratio [OR] = 1.3; 95% confidence interval [CI] = 1.0, 1.6) at ages up to 11–12 years (n = 191). Hg concentration was also associated with wheezing (OR = 1.2; 95% CI = 1.0, 1.3), asthma medication use (OR = 1.4; 95% CI = 0.97, 2.0), and airway hyperresponsiveness (OR = 1.2; 95% CI = 1.0, 1.3). Further adjustment for fish consumption did not change the results appreciably. Conclusions: Low-level Hg exposure was associated with asthma and blood profile changes in school-age children.